1988
DOI: 10.1055/s-2006-962353
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from the Roots ofSedum cressipes

Abstract: Continuing research on flavonoid compounds of the genus Centaurea (1, 2), we report here six methoxylated flavonoids and one triterpenic acid from the aerial parts of Centaurea cuneifolia Sm. (Cornpositae) which has not been investigated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Ð 13 C NMR [75 MHz, CD 3 OD, δ (ppm)]: δ = 110.9 (C-2, C-6), 122.7 (C-1), 140.1 (C-4), 146.9 (C-3, C-5), 171.0 (CO 2 H). NMR data are in accordance with the literature (Sun et al, 1988;Nawwar et al, 1982 …”
Section: Auto-oxidation Of -Carotene Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…Ð 13 C NMR [75 MHz, CD 3 OD, δ (ppm)]: δ = 110.9 (C-2, C-6), 122.7 (C-1), 140.1 (C-4), 146.9 (C-3, C-5), 171.0 (CO 2 H). NMR data are in accordance with the literature (Sun et al, 1988;Nawwar et al, 1982 …”
Section: Auto-oxidation Of -Carotene Methodssupporting
confidence: 89%
“…Although the exhibited 1 H NMR spectral data of compounds 1, 3 and 4 have been compared with laricetrin and laricetrin-glycosides previously published (Niemann, 1973;Khetwal et al, 1988), in this present paper their structures were confirmed by both HMBC and HMQC spectra. The chemical shifts observed in the 1 H NMR spectrum and attributed to H-2Ј and H-6Ј of laricetrin by Niemann (1973) and Khetwal et al (1988) are inconsistent with the AB pattern expected for ring B for the laricetrin aglycone.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Frs DS 1 -DS 12 (13.8 g) contained mainly alkaloids and other components exhibiting no UV absorption while frs DS 13 -DS 25 (9.5 g) contained primarily a mixture of glycosides and were subjected to low pressure chromatography on a RP C-18 7 cm  40 cm column using a linear gradient of 250 ml MeOH-H 2 O mixtures ranging from 0 to 100% MeOH, 52 frs (DSA 1 -DSA 52 ) being collected. Frs DSA 15-21 (284 mg) were chromatographed over a polyamide column (35 cm  1 cm) and eluted with MeOH-EtOAc (3:2) to give in subfrs 14-20 after purification by crystallization from MeOH-EtOAc (2:1) 120 mg of paeonoside (3) identified by HRMS, 1 H and 13 C NMR spectrometry (Kamiya et al, 1997;Khetwal et al, 1988;Markham et al, 1978). Frs DSA 23-24 (288 mg) were subjected to gel filtration on Sephadex LH-20 using CH 2 Cl 2 -MeOH (1:1) as eluent, fifty 200 ml subfrs being collected.…”
Section: Extraction and Isolation Of The Flavonoidsmentioning
confidence: 99%
“…In the previous structural proof of kaerophyllin (7), location of the two MeO groups and the methylenedioxy group at 3, 4 and 3', 4' positions, respectively, rested entirely 5'..... 6.71 (dj= 7.8 Hz) 6.53(dJ = 7.8Hz) 108.5 108. 5 6'..... 6.61 (ddj= 7.8, 1.6 Hz) 6.23 (ddj= 7.8, 1.1 Hz) 121.9 122.2 7'a..... 3.02 (ddj = 14.4,4.2 Hz) 2.74(ddJ= 14.4,4.3 Hz) 37.4f 37.3f -och2o-. 5.91 (AB Jab =1.4 Hz) "The assignments of C-l, C-8, and C-V in C6D6 are based upon the unambiguous assignments in CDClj and not upon directly observed long range heteronuclear couplings in this solvent (i.e., C-l, C-8, and C-l' were distinguished in CDC13, not in CgDg).…”
mentioning
confidence: 99%